MANUSIA DAN ALAM: TELAAH REFLEKTIF TERHADAP PERAN DAN FUNGSI SEBAGAI SUBJEK DAN OBJEK DALAM PENDIDIKAN ISLAM - Cecep Nikmatullah; Wasehudin (Journal of Innovation Research and Knowledge, 2022)
This study aims to explore the phenomenology of humans and nature in examining their roles and functions as subjects and objects in Islamic education. Qualitative research with a concept analysis approach is used as written literature and the main source. Data collection and analysis is done by content analysis. The results of the study show that various natural phenomena and phenomena continue to show their activities, even making humans anxious, such as natural disasters, eruptions, volcanic eruptions, fires, droughts, floods and others that occur in human life. This can be seen from the role and function of humans and nature as subjects and objects. Humans as natural objects mean humans are related to the environment, while humans as natural subjects mean humans have the ability to control the environment. Human behavior in controlling nature will greatly determine the behavior of nature in the next phase. Humans must show their existence as servants ('abdullah) who have inspired divine values ​​that are embedded as implementers of God's mandate (caliphate) on earth. The target of Islamic education is human. Education for humans who can humanize humans. Thus, in Islamic education, humans as objects have the position of being monopluralists, namely, although they are different in all aspects, they remain a unity, harmony, harmony, and balance between humans and God, between individuals and society; Humans as individuals are recognized for their rights and obligations, their existence is recognized and respected. So that Islamic education can be achieved according to its objectives. The achievement of the goals of Islamic education is very dependent on the extent to which the ability of Muslims to realize and realize the role of the philosophy of human creation and the function of its creation in this universe. Humans as subjects in Islamic education can be used as a vehicle for the process of transforming Islamic science and culture from one generation to the next. It is hoped that this article can motivate educational philosophy researchers in following up on a holistic study of various phenomena of natural damage in various perspectives, especially the perspective of educational philosophy